AAT workbook for practice and revision: Cost accounting and budgeting - Association of Accounting Technicians (London Financial training courses Limited, 1989)
This workshop provides revised and practical cost samples for accounting students.
asm; 23/01/19
Loans
Keywords: Finance (workbook); Accounting and budgeting